Two Human Cases of Fatal Meningoencephalitis Associated with Potosi and Lone Star Virus Infections, United States, 2020–2023 - Chiu, Charles Y.; Godasi, Raja Rama; Hughes, Holly R.; Servellita, Venice; Foresythe, Kafaya; Tubati, Asritha; Zorn, Kelsey; Sidhu, Sukhman; Wilson, Michael R.; Bethina, Sai Varun; Abenroth, Daniel; Cheng, Yee; et al. (Emerging infectious diseases, 2025)
We used clinical metagenomic next-generation sequencing of cerebrospinal fluid to investigate bunyavirus infections in 2 immunocompromised patients in the United States who had fatal meningoencephalitis. Potosi virus has been isolated from mosquito vectors and Lone Star virus from tick vectors. These findings highlight the power of metagenomic next-generation sequencing in broad-based, agnostic detection of emerging viral infections that test negative using conventional targeted diagnostic methods.